(3QSGdI CHj EjdjG GdfUjHjfis - (3GHf GdSfj , CHh GjdjG eWQGf fUjHjf (B- (3GjdjG Hf GdSfj , eWQGf fUjHjfs
(3ChdgG (B:s
(3QSGdI CfTCgG GdCH EjdjG eWQGf fUjHjf s
(3BNQgG (B:s
(3aHTaGYI GdSjOI Ce GdfhQ eQje GdWGgQI GdHJhd hLejY GdbOjSjf Bejf s
(3jQLY JGQjN fSNgG Edi SfI (B1242(3es
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B29s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds